An Analysis of Personification in New International Version Bible: Philippians Book - Christian Deendomu; Diana Anggraeni; Bob Morison Sigalingging (Riviera Publishing, 2023)
Objectives: This study aims to identify the types of personification and explain the meanings of personification in the Book of Philippians as well as explain the relationship between the meaning of personification and the entire contents of the Book of Philippians. Method: The research method used is descriptive-qualitative to collect data. Method qualitative this can used on one data time or in approach data collection during period time certain. Results: The results of this study indicate that there are 55 personification data, namely 20 noun personification data, 14 verb personification, 13 adjective personification, and 8 adverb personification. In this study, conceptual meaning has a dominant and important role because conceptual meaning is needed when the Apostle Paul conveys a message about a joyful life in the Lord Jesus, even in times of joy and sorrow for believers in Philippi. Conclusion: In Overall, the essence of the book of Philippians discuss about jo, speech gratitude, obedience, responsibility Answer, unit faith in Jesus Christ, fellowship in news The Bible, as well fellowship in suffering Jesus Christ as well as fellowship in power spirit. resurrection. All That is experience experienced by the Apostle Paul when spread news Gospel to the believers in Philippi